29 dates - De la Cruz, Melissa, 1971- (Inkyard Press, 2018)
"Ji-su's traditional South Korean parents are concerned by what they see as her lack of attention to her schoolwork and her future. Working with Seoul's premiere matchmaker to find the right boyfriend is one step toward ensuring Ji-su's success, and going on the recommended dates is Ji-su's compromise to please her parents while finding space to figure out her own dreams. But when she flubs a test then skips out on a date to spend time with friends, her fed-up parents shock her by shipping her off to a private school in San Francisco. Where she'll have the opportunity to shine academically--and be set up on more dates!"--